2012
DOI: 10.1021/ie2018417
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Conversion of Syngas into Higher Alcohols over Carbide Catalysts

Abstract: The salt was dried to constant weight at 110 °C. In the calculation of the loading it is assumed that this treatment has removed all water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 124 publications
(186 reference statements)
5
26
0
Order By: Relevance
“…S4). The focus of the present study is the formation of oxygenates which was reported to be enhanced by potassium promotion [20,22,23,29,37]. Due to the high CO2 selectivities, it is of interest to compare the formation towards oxygenates and hydrocarbons without CO2.…”
Section: Effect Of Potassium Promotion On the Activity And Selectivitmentioning
confidence: 97%
See 1 more Smart Citation
“…S4). The focus of the present study is the formation of oxygenates which was reported to be enhanced by potassium promotion [20,22,23,29,37]. Due to the high CO2 selectivities, it is of interest to compare the formation towards oxygenates and hydrocarbons without CO2.…”
Section: Effect Of Potassium Promotion On the Activity And Selectivitmentioning
confidence: 97%
“…Prior to the Fischer-Tropsch experiments, the catalyst samples are treated in 50 ml/min/gcat hydrogen at atmospheric pressure and 400°C with a ramp rate of 5°C/min for 4.5 h to reduce the catalyst and to remove the oxide layer formed during the passivation step. This pretreatment is commonly reported in literature [24,29,30]. Exception is made for one in situ prepared non-promoted catalyst, which was not passivated.…”
Section: Catalyst Testingmentioning
confidence: 99%
“…A small amount of alcohols was found in their products at high reaction pressure, while the synthesis of hydrocarbons was restricted and the production of alcohols was promoted by addition of K 2 CO 3 [25]. Afterwards, numerous studies [26][27][28][29][30][31][32] were carried out to obtain a catalyst with high activity and superior alcohol selectivity by adjusting process conditions (pressure, temperature, space velocity, etc.) and promoters (alkali metals, transition metals, supports, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…Higher temperatures are favourable for the formation of HCs as well as CO 2 via a water gas shift reaction on K/Mo 2 C catalysts . The increased CO 2 concentration at steady state alters the CO/H 2 ratio in the reactor zone and influences the CO insertion process followed by higher alcohol formation …”
Section: Resultsmentioning
confidence: 99%